Search for R-parity violating supersymmetry in pp collisions at root s=13 TeV using bjets in a final state with a single lepton, many jets, and high sum of large-radius jet masses - Sirunyan, A. M. (2018)
Results are reported from a search for physics beyond the standard model in proton-proton collisions at a center-of-mass energy of root s=13TeV. The search uses a signature of a single lepton, large jet and bottom quark jet multiplicities, and high sum of large-radius jet masses, without any requirement on the missing transverse momentum in an event. The data sample corresponds to an integrated luminosity of 35.9 fb(-1) recorded by the CMS experiment at the LHC. No significant excess beyond the prediction from standard model processes is observed. The results are interpreted in terms of upper limits on the production cross section for R-parity violating supersymmetric extensions of the standard model using a benchmark model of gluino pair production, in which each gluino decays promptly via (g) over tilde -> tbs. Gluinos with a mass below 1610 GeV are excluded at 95% confidence level. (c) 2018 The Author(s). Published by Elsevier B.V. This is an open access article under the CC BY license (http://creativecommons.org/licenses/by/4.0/). Funded by SCOAP(3).